ENGLISH TEACHERS’ PERCEPTION ON TEACHER PROFESSIONALISM - Nida Husna; Khairunnisa Fitri; Wiwi Rhamadina; Fahriany Fahriany; Didin Nuruddin Hidayat; Afifah Linda Sari (LET: Linguistics, Literature and English Teaching Journal, 2022)
This paper aims to investigate English teachers’ perceptions of teacher professionalism. A qualitative method with a descriptive design was employed in the present stud. The researchers employed a set of adapted questionnaires on teacher professionalism (Tichenor & Tichenor 2009), consisting of five critical typologies of teacher professionalism. The questionnaire was distributed to 14 English teachers of senior high schools in Pangkal Pinang and the Blangkejeren district. They were chosen as the sample through the purposive sampling technique. Furthermore, a semi-structured interview also has been completed to support the data. The findings of this study indicated that most of the teachers agree with the characteristic of a professional teacher proposed by Sockett (1993). The study also revealed that professionalism is one of the critical aspects that teachers should possess.